Laboratory Assessment of Drought Tolerance in Chickpeas Varieties and Lines (Eurasian Journal of Research, Development and Innovation, 2023)
The creation of productive chickpea varieties and lines, selection materials that are resistant to the current global drought remains an urgent issue. For this purpose, the drought tolerant of chickpea lines brought from the international centers of ICARDA was analyzed in laboratory conditions and the results of the analysis are presented in this article.